2009
DOI: 10.1021/jm900631m
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Decoy That Interrupts G93A-Superoxide Dismutase Gain of Interaction with Malate Dehydrogenase Improves Survival in an Amyotrophic Lateral Sclerosis Cell Model

Abstract: Human G93A-superoxide dismutase-1 (G93AhSOD1) mutation causes amyotrophic lateral sclerosis (ALS) in rodents and humans. Recent observations indicate gain of interaction of G93AhSOD1 with cytosolic malate dehydrogenase (MDH1) and subsequent impairment in the malate aspartate shuttle which is vital to neurons. Using fluorescence resonance energy transfer (FRET), we screened an MDH1 derived peptide library for a decoy that would interrupt the G93AhSOD1-MDH1 interaction. A specific 23 amino acid blocker of this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Subsequently, increased binding of HIF‐1α to the HRE in the 5′ promoter region of VEGF enhances its expression, leading to increased intracellular levels of VEGF . In addition to hypoxia, intracellular levels of HIF‐1α are upregulated by proinflammatory cytokines, such as IL‐1 and TNF growth factors , and mutant proteins such as mSOD1 , which is presumably caused by suppression of HIF‐1α‐PHD . Elevated intrathecal levels of a variety of proinflammatory cytokines in ALS patients are likely to contribute to the increase in the level of HIF‐1α.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, increased binding of HIF‐1α to the HRE in the 5′ promoter region of VEGF enhances its expression, leading to increased intracellular levels of VEGF . In addition to hypoxia, intracellular levels of HIF‐1α are upregulated by proinflammatory cytokines, such as IL‐1 and TNF growth factors , and mutant proteins such as mSOD1 , which is presumably caused by suppression of HIF‐1α‐PHD . Elevated intrathecal levels of a variety of proinflammatory cytokines in ALS patients are likely to contribute to the increase in the level of HIF‐1α.…”
Section: Discussionmentioning
confidence: 99%
“…Cell lines mostly included standard SOD1 G93A transfected mice cells. However, other G93A-transfected sources included SH-SY5Y cells ( Carri et al, 1997 ; Goos et al, 2007 ; Pesaresi et al, 2011 ), NSC-34 cells ( Liu et al, 2002 ; Ferri et al, 2008 ; Mali and Zisapel, 2009 ; Crippa et al, 2010 ), yeast ( Gunther et al, 2004 ; Kloppel et al, 2010 ), and bacteria ( Singh et al, 1998 ).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that PCK1 is involved in the processes of small molecule biochemistry, carbohydrate metabolism, molecular transport, and response to drugs including 5-tert-butyl-3H-1,2-dithiole-3-thione (TBD), 3H-1,2-dithiole-3-thione (D3T), and its analogues 4-methyl-5-pyrazinyl-3H-1,2-dithiole-3-thione (OLT) [63]. MDH1 (malate dehydrogenase 1) in this pathway has been reported to be relevant with drug toxicity [64, 65]. Another gene in this pathway worth mentioning is AQP1 (Aquaporin-1), which was highly expressed in endothelial cell membranes and involved in water transfer across or into these cells.…”
Section: Resultsmentioning
confidence: 99%